2-{(1E)-[(E)-2-(2,6-Dichlorobenzylidene)hydrazin-1-ylidene]methyl}phenol: crystal structure, Hirshfeld surface analysis and computational study - Manawar, Rohit B.; Gondaliya, Mitesh B.; Shah, Manish K.; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2019)
The title Schiff base compound, C14H10Cl2N2O, features an E configuration about each of the C N imine bonds. Overall, the molecule is approximately planar with the dihedral angle between the central C2N2 residue (r.m.s. deviation = 0.0371 A˚ ) and the peripheral hydroxybenzene and chlorobenzene rings being 4.9 (3) and 7.5 (3), respectively. Nevertheless, a small twist is evident about the central N—N bond [the C—N—N—C torsion angle = 172.7 (2)]. An intramolecular hydroxy-O—HN(imine) hydrogen bond closes an S(6) loop. In the crystal, – stacking interactions between hydroxy- and chlorobenzene rings [inter-centroid separation = 3.6939 (13) A˚ ] lead to a helical supramolecular chain propagating along the b-axis direction; the chains pack without directional interactions between them. The calculated Hirshfeld surfaces point to the importance of HH and Cl...H/H...Cl contacts to the overall surface, each contributing approximately 29% of all contacts. However, of these only Cl...H contacts occur at separations less than the sum of the van der Waals radii. The aforementioned – stacking interactions contribute 12.0% to the overall surface contacts. The calculation of the interaction energies in the crystal indicates significant contributions from the dispersion term.